Descriptive account of 18 adults with known HIV infection hospitalised with SARS-CoV-2 infection. Issue 5 (2nd September 2020) - Madge, Sara; Barber, Tristan J; Hunter, Alan; Bhagani, Sanjay; Lipman, Marc; Burns, Fiona
Abstract : Objective: To report on the clinical characteristics and outcome of 18 people living with HIV (PLWH) hospitalised with SARS-CoV-2 infection in a London teaching hospital. Methods: The hospital notes of 18 PLWH hospitalised with SARS-CoV-2 infection were retrospectively reviewed alongside data concerning their HIV demographics from an established HIV Database. Results: The majority (16/18) had positive PCR swabs for SARS-CoV-2, and two had negative swabs but typical COVID-19 imaging and history. Most were male (14/18, 78%), median age 63 years (range 47–77 years). Two-thirds were migrants, nine (50%) of Black, Asian and minority ethnicity (BAME). All were diagnosed with HIV for many years (range 8–31 years), and all had an undetectable HIV viral load (<40 copies/mL). The median CD4 prior to admission was 439 (IQR 239–651), and 10/16 (63%) had a CD4 nadir below 200 cells/mm 3 . Almost all (17/18) had been diagnosed with at least one comorbidity associated with SARS-CoV-2 prior to admission. 3/18 patients died. None received mechanical ventilation. Hospital stay and clinical course did not appear prolonged (median 9 days). Conclusions: Our data suggest that PLWH may not necessarily have prolonged or complex admissions to hospital when compared with the general hospital and national population admitted with COVID-19. Many had low nadir CD4 counts and potentially impaired functional immune restoration. The PLWH group was younger than generally reported for COVID-19, and the majority were male with multiple complex comorbidities. These patients had frequent contact with hospital settings increasing potential for nosocomial acquisition and increased risk of severe COVID-19.